2017
DOI: 10.1002/joc.5253
|View full text |Cite
|
Sign up to set email alerts
|

Heat waves in Finland: present and projected summertime extreme temperatures and their associated circulation patterns

Abstract: The number and intensity of individual hot days affecting Finland in the current and future climate is investigated together with the circulation patterns associated with the hot days. In addition, the number, length and intensity of heat waves lasting at least 3 days is also considered. ERA‐Interim reanalysis data and both direct model output and bias‐corrected data for historical and future climate [representative concentration pathway 4.5 (RCP4.5) scenario] simulations from 17 global climate models are anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 20 publications
(29 reference statements)
0
29
0
2
Order By: Relevance
“…It is known that literature lacks a universal definition of HWs (e.g., [16]). The use of upper percentiles in T max and the choice of the least duration of three consecutive days in the adopted definition is consistent (or more strict) with definitions used in other relevant studies [41][42][43][44].…”
Section: Heat Wave Identification Processmentioning
confidence: 59%
“…It is known that literature lacks a universal definition of HWs (e.g., [16]). The use of upper percentiles in T max and the choice of the least duration of three consecutive days in the adopted definition is consistent (or more strict) with definitions used in other relevant studies [41][42][43][44].…”
Section: Heat Wave Identification Processmentioning
confidence: 59%
“…This result resonates somewhat with the results of Kim et al . (), who analysed climate model projections and concluded that the relative change in heatwave duration and occurrence in Finland was larger for northern Finland than southern Finland (they did not consider the magnitude of temperature anomalies). The positive temperature anomalies in May and July 2018 were found to extend throughout the whole depth of the troposphere, from the surface up to ~10km.…”
Section: Discussionmentioning
confidence: 99%
“…In Europe, for example, HWs cause more human fatalities than any other natural hazard (period 1998–2009; European Environment Agency (EEA), ). As many studies have shown, the occurrence of HWs has increased until today (e.g., Alexander et al ., ; Moberg et al ., ; Della‐Marta et al ., ; Perkins et al ., ; Russo et al ., ; Kim et al ., ; Piticar et al ., ). Other studies show further increase for the coming decades in HW frequency, duration, and magnitude due to projected global climate change (e.g., Meehl and Tebaldi, ; Beniston et al ., ; Koffi and Koffi, ; Fischer and Schär, ; Russo et al ., ; ; Zacharias et al ., ; Kim et al ., ; Lhotka et al ., ).…”
Section: Introductionmentioning
confidence: 97%